The effect of six-week plyometric exercises with tabata protocol on some biomotor properties in U-16 male footballers - Aslan, Tahir Volkan (2023)
In modern football, physiological assessments are becoming increasingly important for optimal performance not only in adults but also in youth. The aim of this study was to investigate the effect of six-week plyometric exercises with tabata protocol on some biomotor properties in U-16 male football players. The athletes were randomly divided into 2 groups as experimental (n:12) and control (n:12). The plyometric exercise programme was applied to the experimental group in addition to their own football training 2 days a week for 6 weeks, while the control group only participated in football training. The normality level of the data was determined by Shapiro-Wilk test. Independent Sample T Test for independent groups and Paired Sample T Test for dependent groups were used to analyse the normally distributed data. According to the research findings, a statistically significant difference was found in the pre-test - post-test measurement values of all performance tests of the experimental group and between all performance tests (T-Agility, 20-m sprint, vertical jump, flamingo balance and long jump standing) of the experimental and control groups (p < 0.05). No significant difference was found in the control group (p>0.05). In conclusion, it can be said that six-week plyometric exercises applied with Tabata protocol were effective in the development of some biomotor properties in U-16 male football players.  In this context, it can be stated that plyometric exercises added to training plans can be used as an effective method in the development of performance parameters of athletes.